What do we know about body dysmorphic disorder - Review of current knowledge - Brożyna, Aleksandra; Bydliński, Arkadiusz; Kwiatkowska, Anita; Emerla, Sara; Małek, Natalia; Karłowicz, Konrad; Ciulkiewicz, Łukasz; Pluta, Patryk; Lubomirska, Julia; Figurowska, Patrycja; Hermanowska, Maria (Journal of Education, Health and Sport, 2024)
Introduction Body dysmorphic disorder, also known as dysmorphophobia, is a severe psychiatric disorder characterized by DSM-V as preoccupation with one or more perceived defects or flaws in physical appearance, that are not observable or appear slight to others. BDD can cause significant distress or impairment in social and occupational areas of life. It is often comorbid with other psychiatric conditions like major depressive disorder. Current ways of treatment include a combination of pharmacotherapy and cognitive-behavioral therapy. Aim of the study To summarize current knowledge of body dysmorphic disorder, its pharmacological and non-pharmacological treatment, outline possible areas for further research, and raise the awareness of the disorder. Material and methods The review was based on the PubMed database and was carried out using keywords to determine the latest publications. Summary Body dysmorphic disorder is a relatively common and severe condition that greatly diminishes patients' quality of life. While helpful diagnostic tools exist, BDD diagnosis remains relatively uncommon, posing challenges for patients to receive adequate treatment and continuing their suffering. Despite identifying several factors contributing to the disorder, much remains unknown. Many patients do not respond to standard treatment options, highlighting the need for further studies into the disorder's neurobiology, causes, and alternate treatment approaches to achieve a deeper comprehension of BDD as the number of new cases increases every year.